A study on the attitude of the graduates towards employment / Anith Amalina Amran and Norhalilah Ab Rahman - Amran, Anith Amalina; Ab Rahman, Norhalilah (2014)
The students have conducted the supervision of research throughout this semester. The research report was made in accordance with the supervised format. The research report comprises of 5 chapters that cover several aspects which are introduction, literature review, research methodology, finding and conclusion. In the first chapter, the students describe the background of the study, problem statement, research questions, research objectives, scope of study, significance, and definition of key terms. The students have demonstrated the scholar views in the chapter 2 of literature review. The dependant variable and independent variable were stated along with the conceptual framework. In the chapter 3, the students has describe the research methodology comprise the research method, research design, sampling techniques, sample size, unit of analysis and the conceptual and operational. The data collection method were explained then the students presented the finding of the Pilot study using the Cronbach’ Alpha. After the data collected, the students presented the finding and discussion in the chapter 4 based on the result using the descriptive analysis and Pearson Correlation analysis. Lastly, the students provide the conclusions of the finding by comparing the students’ actual results with the scholar statements.